CHITOSAN BASED PARTICULATE CARRIER OF DITERPENE LACTON OF SAMBILOTO PREPARED BY IONIC GELATION-SPRAY DRYING :EFFECT OF STIRRING RATE AND NOZZLE DIAMETER - Sari, Retno (2014)
Chitosan, a cationic polysaccharide has many advantages as carrier for drug delivery system such as biocompatible, biodegradable and non toxic.Chitosan has amino group that could be crosslinked with polianion such as tripolyphosphate